Effect of long-term use of eurycoma longifolia on the liver - Alfaqeh, Hamoud Hussein Mohammed (2014)
Eurycoma longifolia Jack (ELJ) (Tongkat Ali) is one of the plants of such category. Even though toxicity and safety evaluation studies have been carried out, still a major gap exists in providing scientific base for commercial utilization of the Tongkat Ali’s products with regard to consumer's safety. The water extracts of ELJ has been reported to have a better market value as beverage and capsules1. In our previous study we found that water extract of ELJ caused no damage to hepatocytes in rats when given alone orally for only one week2. The long term consumption of ELJ as beverage among men and women for its vitality during copulation incited us to evaluate its effect on the safety of body organs. However, there is a lack of scientific evidence for such deleterious effects (10). Owing to the lack of published data on the efficacy of long term use of ELJ on some organs, we were prompted to evaluate its effect on the vital organs of the body. In the present study we aimed to determine if long term consumption of ELJ as beverage could have any deleterious effect on the tissues of liver or not.